Hydrazones derivatives from halo-pyridinol: Synthesis and DFT-based theoretical exploration (Kuwait Journal of Science)
Three novel halo-pyridinol-based hydrazone derivatives were synthesized successfully for their virtual optoelectronic properties. These are (E)-2-((2-chloropyridin-3-yl)oxy)-N'-(4-fluorobenzylidene)acetohydrazide (CPFH), (E)-N'-(4-chlorobenzylidene)-2-((2-chloropyridin-3-yl)oxy)acetohydrazide (CCPH), and (E)-2-((2-chloropyridin-3-yl)oxy)-N'-(4-methylbenzylidene)acetohydrazide (CPMH). All these compounds have been extensively characterized using nuclear magnetic resonance and infrared spectroscopic techniques. Additionally, their optoelectronic behavior was investigated using quantum chemical calculations with the ꞷB97XD/6–31+g(d,p) approach. Various properties of the synthesized compounds were explored using density functional theory (DFT) calculations, including NBO (natural bond orbital), NLO (non-linear optical properties), NPA (natural population analysis), and FMO (frontier molecular orbital) analyses. Furthermore, photophysical properties of these compounds were studied using a time-dependent DFT (TD-DFT) approach at the ꞷB97xd/6–31+g(d,p) level. The DFT investigations showed that compound CPMH possesses higher stabilization energy than CCPH and CPFH. © 2025 The Authors